2022
DOI: 10.3390/w14203324
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Four Plant-Based Bio-Coagulants Performances against Alum and Ferric Chloride in the Turbidity Improvement of Bentonite Synthetic Water

Abstract: Due to their cost-effectiveness, low toxicity, and naturally renewable properties, bio-coagulants for water treatment are gaining popularity. In this context, four bio-coagulants were tested for their ability in turbidity reduction in a synthetic bentonite suspension: Opuntia ficus indica (OFI) and Moringa oleifera (MO) seeds, two well-established vegetal materials in the domain of bio-coagulation, and Algerian Aloe vera (AV) and Pinus halepensis seeds (PHS), both of which have received very few or no study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 75 publications
1
18
0
Order By: Relevance
“…As shown in Figure . 6 3, the addition of LB-HCl coagulant to well water resulted in a significant decrease in turbidity values [13]. HCl solution also plays a role in increasing polygalacturonic acid levels and protein levels extracted in Aloe vera, thereby increasing the efficiency of Aloe vera as a coagulant [14]. In this study, it was found that the turbidity removal efficiency decreased in line with the increase in coagulant dose.…”
Section: Optimisation Of Phmentioning
confidence: 62%
“…As shown in Figure . 6 3, the addition of LB-HCl coagulant to well water resulted in a significant decrease in turbidity values [13]. HCl solution also plays a role in increasing polygalacturonic acid levels and protein levels extracted in Aloe vera, thereby increasing the efficiency of Aloe vera as a coagulant [14]. In this study, it was found that the turbidity removal efficiency decreased in line with the increase in coagulant dose.…”
Section: Optimisation Of Phmentioning
confidence: 62%
“…Due to their biodegradability and environmental friendliness, the use of natural coagulants in water treatment has become essential. In recent years, there have been numerous reports of natural coagulants derived from diverse plant species, including Jatropha curcas [15], banana peels [16], bagasse [17], Aleppo pine seeds, prickly pear and Aloe vera mucilage [18]. In accordance with these results, natural coagulants have a high prospect of replacing the traditional chemical coagulant, since they demonstrate promising treatment performance.…”
Section: Introductionmentioning
confidence: 73%
“…The obtained powder is referred to as MOP. A saline extraction was performed according the method described earlier [18]; the resulting mixture is referred to as MOPS. An aqueous extraction was also undertaken for comparison purposes (MOPW).…”
Section: Chemicals and Materialsmentioning
confidence: 99%
“…Although coagulation has been applied as the main surface water treatment process in DWTPs across the world for decades, there are still a number of issues that researchers investigate. They include the application of ecologically friendly biocoagulants, the development of novel hybrid coagulants, and the possibility of increasing the efficiency of surface water purification by combining coagulation with different unit water treatment processes [5,[7][8][9]. Such research is necessary not only for the purpose of overcoming known limitations and disadvantages of conventional coagulation, but also to ensure its continuous applicability in the context of rising challenges [7].…”
Section: Introductionmentioning
confidence: 99%
“…The most pressing problems associated with water treatment via coagulation appear to be the vulnerability of the process to changing NOM concentration and composition, and the consequences of employing metallic salts as coagulants [7,10,11]. Revisiting the topic of surface water purification via coagulation with consideration of both the current and anticipated challenges is necessary.…”
Section: Introductionmentioning
confidence: 99%